Comparative study of impact of marketing strategies of pharmaceutical houses on prescription practices of doctors rural vs urban - Gupta, Shallini; Khajuria, Kanika; Khajuria, Vijay; Kumar, Niraj (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Indian pharmaceutical market is fast going and there is a stiff competition amongst them as single product is marketed by different brand names. The pharmaceutical houses adopt different strategies to influence the physician to promote their products. These strategies are known to influence the prescription behaviour of physician, which may have variable impact among rural and urban doctors. Aim of the study was to compare the impact of marketing strategies of pharmaceutical houses on prescription practices of rural and urban doctors. Methods: The current crossover study was conducted among urban and rural doctors. A questionnaire consisting of 17 questions was presented to the doctors and their responses regarding different aspects of marketing strategies was recorded. Comparison between two groups was done using unpaired t-test. Results: Different strategies had impact on prescription pattern of doctors working in rural and urban institutions. All 17 parameters were affected similarly except e-mailing where urban doctors were more influenced (p=0.005). Conclusions: Present study indicates marketing strategies by different pharmaceutical houses do influence prescription pattern of physicians. Both urban and rural doctors were similarly affected except e- mailing which had more impact on urban doctors.